Studi Perancangan Mesin Pencacah Biji Jagung Menjadi Jagung Halus Dengan Model Pisau Rotary Kapasitas 60 Kg/Jam - Candra Pardede; Franky Sutrisno (Fakultas Teknik UMSU, 2018)
The design of the corn seed chopping machine into fine corn is an alternative to increasing the selling value of farmers' corn, the previous chopper machine was considered to be less efficient because it relied on friction using a dish. This problem prompted the writer to design the corn kernels, on the topic of this discussion the author limited the problems that included machine design in several stages, namely: planning in the form of working drawings, calculating and determining the power and rotation of the driving motor needed to move the engine ; planning and calculating machine elements, including: chopper, shaft, bearing, lubrication, pegs, pulleys, belts, propulsion and frame. The results of this discussion are: The blade made of S45C has a length of 250 mm, and the number of blades used is 3 sets. Shaft made of St 37 in diameter 25 mm. The bearings used are rolling bearings with bearing numbers 205 FBJP. The pegs used have a thickness of 7 mm and a width of 8 mm type is rectangular pegs. Type A pulley with 3 cm drive pulleys and pulleys driven 6.5 cm. Belt-V, type A size 39 number 1. The driving force has a power of 1HP, the actual rotation is 1450 rpm, the rotation planned on the counter shaft is 333 rpm, from this component the engine capacity is 60 kg / hour.